IMMU-17. LEVERAGING CORE EPIGENETIC PROGRAMMING OF IMMUNOSUPPRESSIVE MYELOID CELLS FOR THERAPEUTIC TARGETING OF GLIOBLASTOMA. (14th November 2022) - Bayik, Defne; Bartels, Cynthia; Lovrenert, Katreya; Zhang, Duo; Watson, Dionysios; Kay, Kristen; Lee, Juyeun; Vogelbaum, Michael; Fan, Yi; Scacheri, Peter; Lathia, Justin
Abstract: Accumulation of various immunosuppressive myeloid cells, including myeloid-derived suppressor cells (MDSCs), facilitates progression and treatment resistance of glioblastoma (GBM). We previous demonstrated that monocytic MDSCs (mMDSCs) but not granulocytic MDSCs (gMDSCs) infiltrate tumors in mouse models and patients, and that nonspecific targeting of mMDSCs with chemotherapies provided therapeutic benefit in preclinical models of GBM. To investigate the differential role and trafficking of mMDSCs versus gMDSCs in GBM, we adoptively transferred these cells into tumor-bearing mice. Mice that received mMDSCs succumbed to disease at an earlier point compared to control mice or mice that received gMDSCs. To delineate the cellular basis of this distinct behavior of MDSC subsets, we performed assay for transposase-accessible chromatin using sequencing (ATAC-seq) and observed that cell adhesion-related genes were significantly enriched in open chromatin regions of mMDSCs as opposed to gMDSCs. Aligned with this epigenetic profile, mMDSCs from blood and tumors had significantly higher surface integrin β1 expression compared to gMDSCs in both mouse models and GBM patients. To evaluate the functional role of these integrins, we pre-treated mMDSCs with anti-integrin β1 prior to adoptive transfer. Blockade of surface integrin β1 interfered with the pro-tumorigenic role of mMDSCs, as the survival span of mice receiving these cells was similar to that of vehicle controls. Further analysis of the ATAC-Seq data revealed that dipeptidyl peptidase-4 (Dpp4), an interacting partner of integrin β1, was more accessible in mMDSCs compared to gMDSC. Consistently, bone marrow-derived mMDSCs in mouse and tumor-infiltrating mMDSCs in GBM patients expressed high levels of Dpp4. Pharmacological inhibition of Dpp4 reduced chemotaxis of mMDSCs in vitro and extended survival duration of mice with tumors. The findings from this study have broad implications across cancer types to modulate immunosuppressive myeloid cells by leveraging these novel insights into their adhesion mechanisms.